Disain & Simulasi Rangkaian Pentriger SCR Untuk Penyearah Terkendali Setengah Gelombang Tiga Fasa - Effendi Effendi; M. Agil Haikal (Jurnal JEETech, 2023)
One of the sub-subjects that studied in the power electronics course is the AC to DC converter in the form of a three-phase half-wave controlled rectifier where the output voltage can be controlled by adjusting the SCR gate trigger delay angle, in this research the author design and simulates an SCR triggering circuit for three-phase half-wave controlled rectifier where the components that used among others a three-phase step down transformer where the output functions as a reference signal to determine the starting point (30o) and end point (150o) of the triggering delay angle, also used as a power source for the system, the Op-Amp functions as a comparator for a three-phase rectifier (Vd) with a DC voltage (Vreference), it also functions to compare a triangle wave with a DC voltage to control the delay angle or trigger angle (α) of the SCR. The trigger pulses that given to the SCR1, SCR2, and SCR3 are carried out simultaneously in the same time by using one pulse, the average output voltage resulting from the SCR trigger circuit design in this research is relatively the same as the value obtained using mathematically calculations where the load used in form of resistive